Implementasi Karakter Peduli Sosial Dalam Taruna Siaga Bencana (TAGANA) - Apriliyani, Ayuni Laras; Lestari, Ria Yuni; Bahrudin, Febrian Alwan (Academy of Education Journal, 2024)
The study aims to know: (1) a work program in disaster alert caduna, (2) to know the factors behind and impediment to the implementation of the socially conscious character of the disaster alert in the city of cilegon. The study involves a descriptive qualitative method. Data collection is conducted with interviews, observation, and documentation and data analysis and triangulation. This study suggests that tagana's work program of the city of cilegon was designed in a comprehensive way, involving stages that included prabdisaster, disaster relief, and post disaster recovery. Moreover, implementation of social concern character at every stage of a tagana work program demonstrates a commitment to provide effective and sustained help to affected communities. In the aspect of prabdisaster, a preventive approach and preparation before disaster are considered crucial, while in times of disaster, a quick and effective response is needed. It also focuses on post disaster recovery, including actions such as search and relief, medical assistance, evacuation, relief distribution, psychosocial counseling, education, and reporting and coordination. Then, contributing factors in this process include community participation that is considered a key element in disaster relief. Stakeholder coordination is also identified as a critical contributing factor to ensure an effective and coordinated response in disaster situations. As for the disruptive factors that can affect the implementation of the social care character in tagana city cilegon, which isa diversity of human resources in organizations, financial and equipment limitations, technical difficulties in the field, activation of varying members, and resource limitations in general are a challenge faced.